2019
DOI: 10.1007/s10237-019-01273-8
|View full text |Cite
|
Sign up to set email alerts
|

Embedded axonal fiber tracts improve finite element model predictions of traumatic brain injury

Abstract: With the growing rate of traumatic brain injury (TBI), there is an increasing interest in validated tools to predict and prevent brain injuries. Finite element models (FEM) are valuable tools to estimate tissue responses, predict probability of TBI, and guide the development of safety equipment. In this study, we developed and validated an anisotropic pig brain multi-scale FEM by explicitly embedding the axonal tract structures and utilized the model to simulate experimental TBI in piglets undergoing dynamic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 68 publications
1
90
2
Order By: Relevance
“…The collection of fresh and unfixed brain and measurements of AA levels in the brain tissue were only performed for the Validation Dataset (n = 9 including 5 RNR TBIs and 4 shams). Both of the injury models used in this study have previously showed to cause mitochondrial dysfunction [6,7] and brain damage such as brain contusion, intracranial hemorrhage, and/or diffuse axonal damage as determined by MRI imaging analysis and pathology analysis [32,[53][54][55]. However, the animals typically recovered quickly, reached the baseline physiology within 1-5 h post injury.…”
Section: Methodsmentioning
confidence: 83%
See 4 more Smart Citations
“…The collection of fresh and unfixed brain and measurements of AA levels in the brain tissue were only performed for the Validation Dataset (n = 9 including 5 RNR TBIs and 4 shams). Both of the injury models used in this study have previously showed to cause mitochondrial dysfunction [6,7] and brain damage such as brain contusion, intracranial hemorrhage, and/or diffuse axonal damage as determined by MRI imaging analysis and pathology analysis [32,[53][54][55]. However, the animals typically recovered quickly, reached the baseline physiology within 1-5 h post injury.…”
Section: Methodsmentioning
confidence: 83%
“…This approach may cause overfitting, dependency of the model to the development dataset, and biased assessment of the prediction performance, especially in multivariate analysis with small size datasets. Repeated random training-testing splitting and repeated k-fold cross-validation techniques, in which data are repeatedly split into independent and non-overlapping development and validation datasets, can be used instead of "all in" approach to prevent overfitting and provide more realistic assessment of the accuracy performance of the biomarker models in diagnosing and predicting the outcomes of new patient(s)/subject(s) [32]. Repeated k-fold cross-validation has superiority over repeated random training-testing splitting because the number of times that each data point is used in the training and testing datasets is the same for all data points.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations